2015
DOI: 10.1186/s40064-015-0787-z
|View full text |Cite
|
Sign up to set email alerts
|

ATM gene mutations in sporadic breast cancer patients from Brazil

Abstract: PurposeThe Ataxia-telangiectasia mutated (ATM) gene encodes a multifunctional kinase, which is linked to important cellular functions. Women heterozygous for ATM mutations have an estimated relative risk of developing breast cancer of 3.8. However, the pattern of ATM mutations and their role in breast cancer etiology has been controversial and remains unclear. In the present study, we investigated the frequency and spectrum of ATM mutations in a series of sporadic breast cancers and controls from the Brazilian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 79 publications
(93 reference statements)
1
11
0
1
Order By: Relevance
“…Patients with germline variants in ATM (P604S) and SMO (R400H) were diagnosed with melanoma at ages significantly younger than the average of all included patients (35 and 42). Heterozygous missense mutations in ATM, including the variant identified in our study, have been postulated to increase the risk for breast cancer and aggressive Hodgkin's lymphoma (Liberzon et al, 2004;Mangone et al, 2015;Offit et al, 2002). An 80-year-old patient was found to have a germline mutation in MLH1 (S406N), a gene implicated in Lynch syndrome.…”
Section: Discussionmentioning
confidence: 66%
“…Patients with germline variants in ATM (P604S) and SMO (R400H) were diagnosed with melanoma at ages significantly younger than the average of all included patients (35 and 42). Heterozygous missense mutations in ATM, including the variant identified in our study, have been postulated to increase the risk for breast cancer and aggressive Hodgkin's lymphoma (Liberzon et al, 2004;Mangone et al, 2015;Offit et al, 2002). An 80-year-old patient was found to have a germline mutation in MLH1 (S406N), a gene implicated in Lynch syndrome.…”
Section: Discussionmentioning
confidence: 66%
“…Mutation c.6067G > A was observed in a patient from Brazil with sporadic breast cancer. In that case, the tumor was diagnosed at the age of 45 and was defined as clinical stage II [ 32 ]. In our case tumor was diagnosed at the age of 49 and the pathologic stage of tumor was defined as T2N1M0.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a PubMed search (up to February 10, ) of the following keywords in the title/abstract of the articles: [‘‘ATM’’] AND [‘‘penetrance’’ OR ‘‘risk’’] AND [‘‘breast’’]. Additional studies were identified by a manual search of references from original articles and reviews.…”
Section: Methodsmentioning
confidence: 99%